Xalpirta mauryi sp. nov. (Coleoptera: Erotylidae: Tritomini) from Southeast Brazil - Pecci-Maddalen, Italo Salvatore De Castro; Lopes-Andrade, Cristiano; Skelley, Paul (Zootaxa, 2019)
Xalpirta mauryi sp. nov. (Erotylidae: Tritomini) is described from Parque Nacional do Itatiaia (in the state of Rio de Janeiro) and Campos do Jordão (in the state of São Paulo), Southeast Brazil. Xalpirta mauryi differs from other described Xalpirta in the uniformly green dorsal coloration, with a metallic sheen, and pronotum without spots or black marks. The pore on the posterior 1/3 of each pronotal edge (present in the other Xalpirta) is apparently absent in X. mauryi. We provide a detailed description of adults, including morphology of mouthparts, and male and female terminalia. Additionally, we discuss the morphological affinities of X. mauryi with other species in the genus and with species of other closely related genera within Tritomini, and provide a new geographical record for X. maderi in Southeast Brazil.